Brisk Walking Untuk Menurunkan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe 2: A Literature Review - Magenda Bisma Yudha; Nur Intan Kartika Sari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: One of the non-communicable diseases (NCDs) that has received a lot of attention is Diabetes Mellitus. Diabetes management is divided into two ways. The first way is with non-drug therapy (non-pharmacological) and second with drug therapy. Drug therapy in the form of oral hypoglycemic drugs or insulin. Non-pharmacological methods with food planning and physical exercise. The type of light physical exercise recommended for patients with type II diabetes mellitus is walking and brisk walking. Objective: To determine the effect of brisk walking to reduce blood glucose levels in patients with type 2 diabetes mellitus. Methods: This review uses the literature review method. Searches were conducted in PubMed, Garuda, and Google Scholar. The search strategy used keywords with "brisk walking", "physical exercise", "glycemic control", "diabetes mellitus, type II",. Results: Seven articles were reviewed in this literature review. Six articles discussed brisk walking, one article discussed the difference in glycemic control in low - high intensity interval training with endurance training. The overall results of this review show that doing physical activity brisk walking has an effect in reducing blood glucose levels, reducing blood glucose levels by 49.75 mg/dL. Physical activity sessions can be done for 3 - 7 sessions per week with a duration of 15 - 60 minutes. Conclusion: The effect of brisk walking is proven to reduce blood glucose levels in patients with type 2 diabetes mellitus.